Re-engineering the City: Platform Ecosystems and the Capture of Urban Big Data - Barns, Sarah (Frontiers in Sustainable Cities, 2020)
Today’s digital platforms occupy sites of strategic exchange in the daily lives of cities. Whether in domains like transportation, shopping, accommodation, dating, or simply, public discourse, the value exchanged and traded via platforms today extends beyond basic urban services to include wider ‘data ecosystems’ of users, producers and consumers. In this article I am principally concerned with how platform services institute and govern data ecosystems, and why these are critical to the future of data-driven urban science and sustainability policy. While urban big data is important as a diagnostic tool for monitoring and evaluating complex urban behaviours, the rise of platform urbanism also points to the co-optation of urban data in the service of platform scale and its co-dependencies. These poses significant challenges not only to informational policy, but also for urban governance settings, in which platform-mediated interactions facilitate powerful but unevenly shared territories of urban intelligence.